2003
DOI: 10.1039/b208365e
|View full text |Cite
|
Sign up to set email alerts
|

The formation of bicyclo[n.2.0]alkan-1-ols from the reaction of the lithium enolates of simple ketones and phenyl vinyl sulfoxideElectronic supplementary information (ESI) available: full experimental details. See http://www.rsc.org/suppdata/ob/b2/b208365e/

Abstract: The enolates generated from cyclopentanone, cycloheptanone or cyclooctanone and LDA at -78 degrees C in THF react with (+/-)-phenyl vinyl sulfoxide under controlled conditions of temperature, reaction time, and concentration. Upon oxidation with MCPBA of the product mixtures, the novel sulfonylbicyclo[3.2.0]heptan-1-ols10-12,sulfonylbicyclo[5.2.0]-nonan-1-ols 16-18, and sulfonylbicyclo[6.2.0]decan-1-ols 21 and 22 in conjunction with alkylated ketones 8, 9, 15, 19 and 20 were obtained from the respective ketone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Thermodynamic Control. In previous work we had shown that, within a 24 h time course experiment, the ratio of sulfinylbicyclooctanols 1 − 3 to the monoalkylated ketone 4 decreased from 91:9 at 15 min reaction time, with the monoalkylated ketone 4 being the only product at 24 h. Likewise, increased reaction temperature promoted the formation of the monoalkylated ketone 4 …”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Thermodynamic Control. In previous work we had shown that, within a 24 h time course experiment, the ratio of sulfinylbicyclooctanols 1 − 3 to the monoalkylated ketone 4 decreased from 91:9 at 15 min reaction time, with the monoalkylated ketone 4 being the only product at 24 h. Likewise, increased reaction temperature promoted the formation of the monoalkylated ketone 4 …”
Section: Resultsmentioning
confidence: 81%
“…Optical rotations were measured on a Jasco P-1020 Polarimeter. Bicyclo[ n .2.0]octan-1-ols 1 − 3 , 5 ,15a 6 , 7 ,15a 8 , 9 ,15a 10 , 24 ,15a and monoalkylated ketone 4 13,46 have been characterized previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vinyl sulfides or selenides have been employed in similar stepwise reactions . In contrast, cyclobutane formation from silyl enol ethers, which are one of the most easily prepared ketone-equivalents, has not been achieved except in a limited number of cases. , A significant problem with some of the reported reactions is that simple α,β-unsaturated esters have reactivity lower than that of esters of alkynyl and allenyl carboxylates and other highly electron-deficient olefines 1 …”
Section: Introductionmentioning
confidence: 99%